Análise retrospectiva e tendências do serviço de inspeção do estado de São Paulo - Garnica, Maria Fernanda [UNESP] (2014)
Considering the importance of sanitary inspection of animal products , the constitutional responsibility delegated to the State and the frequent economic and legislative changes in this sector , aimed to the realization of a diagnosis of the situation Inspection Service Sao Paulo - SISP , proposing is conducting a retrospective analysis of his early period to the present day and , while exploring possible trends that in order to assist in planning future actions and demands of this important state of the federation service. The survey was developed through an analytical process of a set of documents belonging to sanitary inspection obtained in Inspection Center for Animal Products - CIPOA and managerial human resources unit of the Coordination of Agricultural Defense - CDA . The results showed that the economic policies of decentralization suffered by the State of São Paulo in the 90s and normative techniques for the production of published in the federal and state levels in the corresponding period of research directly influenced foods in the design and sizing of the service process state inspection. The surveys of technical and health challenges, like the index of 1.36% of cysticercosis' prevalence in 2011 in cattle slaughtered in state stores and analyzes Drip Test within the legal standard in frozen chicken carcasses originating from state industries, show that may have faults in the capture of official data despite the satisfactory numbers. New legal requirements such as Good Manufacturing Practices are not properly implemented in registered establishments indicates the need for more effective action by the tax inspection service with specific training to analyze and check the manual for your staff . The results showed a need for an update on legislation specifies the service because the current state technical regulations have become outdated before preconizações approaches and the food industry . For a perceptive next ...